تقييم معرفة ومواقف مدرسي التعليم الابتدائي حول الأسنان والأذيات الرضية وتدبيرها الاسعافي في مدينة اللاذقية - بدر, فائق (Latakia University Journal -Medical Sciences Series, 2018)
خلفية البحث : يقع على عاتق مدرسي التعليم الأساسي مسؤولية بناء التلاميذ معرفياً واخلاقياً , وارساء اللبنات الأولى في حياتهم المعرفية والسلوكية , ولكي يقوم المدرسون بذلك يجب أن يمتلكوا : المعارف, القدرات, والوسائل اللازمة لنقل ما لديهم من معارف وقيم لطلابهم. تهدف هذه الدراسة إلى تقييم معرفة المدرسين حول الصحة الفموية والأسنان, وتقييم موقفهم العملي الاسعافي في حال وقوع أذيات رضية للأسنان في المدرسة . مواد البحث وطرائقه :تمَ اجراء الدراسة في عشرة مدارس حكومية للتعليم الأساسي اختيرت بشكل عشوائي في مدينة اللاذقية , وفي هذه المدارس تمَ توزيع استبيان مؤلف من (30) سؤالاً على (260) مدرساً ومدرسةً , استبعد منهم (11) استبياناً لعدم الاجابة التامة على الأسئلة . كانت اسئلة الإستبيان متنوعة ما بين ديموغرافية اجتماعية , معرفية حول الصحة الفموية والأسنان , وسلوكية عملية ايذاء الأذيات الرضية في حال حدوثها في المدارس . النتائج :بينت الدراسة أن هناك نقصاً واضحاً في معلومات مدرسي التعليم الأساسي حول الصحة الفموية والأسنان سواءً أكانت مؤقتة أو دائمة ( بزوغاً – عدداً ) , كما أن هناك نقصاً في معارفهم فيما يخص الأذيات الرضية التي تقع في المدارس و الاسعافات الأولية التي يمكن تقديمها للطفل ريثما يصل إلى مركز تقديم العون الطبي اللازم . الخلاصة :إن الدور الساسي لمدرسي التعليم الأساسي سواءً في نقل العلوم الأساسية أو ارساء القواعد الأخلاقية والقيم لدى عدد كبير من الأطفال في مرحلة النمو والتطور الجسدي والعقلي والمعرفي يفرض أن يمتلك هؤلاء المدرسين المعارف والقدرات اللازمة للقيام بهذه المهمة , وهذه ليست مسؤوليتهم وحدهم وانما مسؤولية المجتمع ككل . Research Background It is the responsibility of teachers at the basic education stage to construct the pupils intellectually and morally, and to lay the first building blocks in their cognitive and behavioral life. In order for teachers to do so, they must possess: the knowledge, the abilities and the means to convey their knowledge and values ​​to their students. The aim of this study is to assess the teachers' knowledge about oral health and teeth, and to assess their practical and ambulatory position in the event of traumatic dental injuries in school. Research materials and methods The study was conducted in ten public schools for basic education. All schools were randomly selected in the city of Latakia. In these schools, a questionnaire of 30 questions was distributed to 260 teachers (both male and feamle). 11 questionnaires were excluded for not answering the questions completely. The questions ranged from social demographics to oral and dental health, and the behavior of traumatic injury in schools. Results The study showed that there is a clear lack of information about basic and temporary oral and dental health (emergence - number). There is also a lack of knowledge on the part of these teachers regarding the harmful effects of the teeth and the first aid that can be given to the child while awaiting the necessary medical assistance. Conclusion The central role of teachers in basic education, whether in the transfer of basic sciences or in the establishment of ethical and moral norms among a large number of children in the stage of the physical, mental and informational development, requires that these teachers possess the knowledge and capabilities necessary to carry out this task.